The United nations convention against corruption: A successful example of international action against economic crime - Vlassis Dimitri (Temida, 2012)
This article briefly outlines the progress made in recent years in the development of an international legal framework to combat economic crime, with a specific focus on the United Nations Convention against Corruption. The author notes the impressive progress made by the international community in both the creation and implementation of the Convention, particularly through the adoption of the Implementation Review Mechanism.